2017
DOI: 10.1177/1687814017716639
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and reinforced mechanism of the stainless steel wire mesh–reinforced Al-matrix composite plate fabricated by twin-roll casting

Abstract: Taking the 304 stainless steel wire mesh as reinforcement, Al 1060 as matrix, a solid-liquid cast-roll bonding process based on the vertical twin-roll casting was presented to fabricate the stainless steel wire mesh-reinforced Al-matrix composite plate. Optical microscope and scanning electron microscope were used to observe the microstructure of bonding interface, and the mechanical properties were investigated through tensile test and three-point bending test. The observation results show that there is no ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…In all cases regardless to reduction magnitude the destruction of mesh inlets was observed. The failure mode of wire mesh inlets observed in this research corresponds to that one described by previous authors [4][5][6][7]. The fracture is located at the zones of wires intersection as presented in the figure 3 (a).…”
Section: Figure 2 -Finite Element Model Of the Initial Workpiece In Qsupporting
confidence: 80%
See 2 more Smart Citations
“…In all cases regardless to reduction magnitude the destruction of mesh inlets was observed. The failure mode of wire mesh inlets observed in this research corresponds to that one described by previous authors [4][5][6][7]. The fracture is located at the zones of wires intersection as presented in the figure 3 (a).…”
Section: Figure 2 -Finite Element Model Of the Initial Workpiece In Qsupporting
confidence: 80%
“…Huang Теорія і практика металургії [7]. In all above-mentioned papers authors reported about significant rise of mechanical properties of composites due to application of wire mesh such as fracture toughness [2][3] and tensile strength [3][4][5][6][7]. Among all mentioned processes, for aluminum matrix, roll bonding seems to be the most perspective, since it allows much higher rate of manufacturing, it is simple to control the technology and there is no constrains in length of the product.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this method was not limited by a variety of metals (Xunzhong et al, 2013). Also in order to manufacture composite reinforced by wire, the EXW were used (Los et al, 2010;Huagui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A metal mesh, widely used in agricultural, industrial, transportation, and machine protection sectors, is a common type of metal screen consisting of parallel rows and intersecting columns [20][21][22][23]. A metal mesh can be made using intersecting wires by typically joining them together through welding or weaving.…”
Section: Introductionmentioning
confidence: 99%